Indonesian Islamic Children’s Literature: the Lexical Choices in the Religious Teachings - Laily Martin (English Language in Focus (ELIF), 2018)
The study discusses Islamic religious teachings presented in the Indonesian Islamic children’s literature through the uses of the lexical choices. The discussion covers the religious concepts and practices. For the purpose, the data were taken from five sample children story books of Seri Kalimat thoyyibah which is written by and translated by an Indonesians. The lexical choices presenting the Islamic religious teachings were analyzed by implementing the corpus method and using semantic theories of semantic field and relations. The analysis was also seen from the perspective of the characters’ age by referring to the idea of children psycholinguistic development. The findings show that the lexical choices presenting the concepts of Islamic teachings are mostly unsuited the age of the children characters, as well as the children target readers. This raises concern on the stories comprehensibility. On the other hand, the verb choices describing Islamic practices are friendlier to children readers.